Sistem Informasi Manajemen Produksi Kopi Berbasis Web - Nisfa Laili; Muhammad Fakhriza; Adnan Buyung Nasution (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
Coffee is a beverage made by brewing coffee beans that have been roasted and ground into coffee powder. The process of coffee before it can be drunk goes through a long process, namely from harvesting coffee beans that have been cooked and then drying the coffee beans before they become grain coffee. The next process is roasting the coffee beans and then grinding or grinding them into coffee powder before the coffee can finally be drunk. Coffee continues to grow until now it has become one of the most popular drinks in the world. It is consumed by various groups of people. Likewise with the Oro Coffee Gayo factory. The Oro Coffee Gayo factory also produces coffee starting from drying, roasting and grinding or roasting until it becomes coffee powder and sells it to the public. Not only that, the Oro Coffee Gayo factory also provides export-worthy places for coffee production until it is really exportable. Therefore we need a coffee production management information system at oro Coffee Gayo to facilitate work, facilitate management and data storage, which can help and facilitate performance, so that the process is carried out more effectively and accurately. and it is hoped that this system can be implemented and developed even better.